Reinhart Maurach. Life and work of a twentieth century German criminal lawyer - Muñoz Conde, Francisco (EUNOMÍA. Revista en Cultura de la Legalidad, 2021)
This article aims to offer a thorough revision of Professor Reinhart Maurach’s vital and academic career, with particular emphasis to his complex relation with the national socialist regime, his partaking in the Second World War and his further intervention during the Nuremberg Trials.